Surface Chemistry of Nanohybrids with Fumed Silica Functionalized by Polydimethylsiloxane/Dimethyl Carbonate Studied Using 1H, 13C, and 29Si Solid-State NMR Spectroscopy - Iryna S. Protsak; Yevhenii M. Morozov; Dong Zhang; Volodymyr M. Gun’ko (Molecules, 2021)
The investigation of molecular interactions between a silica surface and organic/inorganic polymers is crucial for deeper understanding of the dominant mechanisms of surface functionalization. In this work, attachment of various depolymerized polydimethylsiloxanes (PDMS) of different chain lengths, affected by dimethyl carbonate (DMC), to silica nanoparticles pretreated at different temperatures has been studied using 29Si, 1H, and 13C solid-state NMR spectroscopy. The results show that grafting of different modifier blends onto a preheated silica surface depends strongly on the specific surface area (SSA) linked to the silica nanoparticle size distributions affecting all textural characteristics. The pretreatment at 400 °C results in a greater degree of the modification of (i) A-150 (SSA = 150 m2/g) by PDMS-10/DMC and PDMS-1000/DMC blends; (ii) A-200 by PDMS-10/DMC and PDMS-100/DMC blends; and (iii) A-300 by PDMS-100/DMC and PDMS-1000/DMC blends. The spectral features observed using solid-state NMR spectroscopy suggest that the main surface products of the reactions of various depolymerized PDMS with pretreated nanosilica particles are the (CH3)3SiO-[(CH3)2SiO-]x fragments. The reactions occur with the siloxane bond breakage by DMC and replacing surface hydroxyls. Changes in the chemical shifts and line widths, as shown by solid-state NMR, provide novel information on the whole structure of functionalized nanosilica particles. This study highlights the major role of solid-state NMR spectroscopy for comprehensive characterization of functionalized solid surfaces.